(3GdOQ GdfXje aj aVGFd GdbQBf GdYXjes - (3GdjGpaYj, Yaja GdOjf, YHO Gddg Hf CSYO Hf Ydj, J(B768(3g`s ((3eMeO eUWais)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj GWdY ef BaGb cJGHg GdYRjR fjQGf CVGM GdZQQ hHYO aEf Gddg SHMGfg hJYGdi LYd cJGHg GdYRjR ddCOhGA TaGA adeG JMbbJ Pdc hCJbfJg aQCjJ Cf CLeY aj gPG GdcJGH Hjf GdHQb GddGeY hGdZjK GdgGeY JCdja GdbGVj CHh HcQ (B( (3cPG (B) (3hSejJg (B: (3HGdOQ GdfXje aj aVGFd GdbQBf GdYXje s
(3BNQgG (B:s
(3hgj QbjI dcd hLY hEPG cJHJ hEPG eQV CMO YhRg HGdeYhPJjf aEPG cGf eQV GdehJ ghfJg Ydjg hCfaJ (B( (3cPG (B) (3GdfaN Ohf GdQjb hef bQCgG YfO fheg Bef ef GdLf hGdEfS hGdhShGS s
(3JHUQI GdYfhGf (B:s
(3LGA aj cTa GdXfhf (B1 / 736 : (3GdOQ GdfXje ddTjN CHj YHO Gddg eMeO Hf CMeO GdNRQLj GdeYQha HGHf GdNTGH Gdjefj J (B567 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 72s
(3eYLe GdeDdajf (B2 / 229s
(3GdOQQ GdcGefI (B2 / 151s
Keywords: (3GdJaSjQ hYdhe GdbQBfs